2019
DOI: 10.1016/j.ctcp.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, characteristics, expenditure and predictors of complementary medicine use in Australians living with gastrointestinal disorders: A cross-sectional study

Abstract: Aims: To determine the prevalence, characteristics, expenditure and predictors of complementary medicine (CM) use in Australian adults living with gastrointestinal disorders (GID). Methods:A cross-sectional study involving 2,025 Australian adults was conducted. Participants were recruited through purposive convenience sampling. Descriptive statistics were conducted to report the prevalence of people living with GIDs and their CM use, including CM products, mindbody practices and CM practitioner services. Chi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…These clinical features include; IBS, 1 GERD, 8 gastritis, 12 heartburn, 1 , 3 non-steroidal anti-inflammatory drug use, 4 older than 60 years; 3 reproductive females, 4 mental health co-morbidities 9 and history of GIT surgery. 73 The justification for these exclusions was rarely described and excluding such conditions may hinder CM practitioners whose patient population is characterised by a greater proportion of women, 74 GIT, 16 mental health co-morbidities 75 and chronic, complex conditions. 16 For example, no included articles justified the rationale for IBS exclusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These clinical features include; IBS, 1 GERD, 8 gastritis, 12 heartburn, 1 , 3 non-steroidal anti-inflammatory drug use, 4 older than 60 years; 3 reproductive females, 4 mental health co-morbidities 9 and history of GIT surgery. 73 The justification for these exclusions was rarely described and excluding such conditions may hinder CM practitioners whose patient population is characterised by a greater proportion of women, 74 GIT, 16 mental health co-morbidities 75 and chronic, complex conditions. 16 For example, no included articles justified the rationale for IBS exclusion.…”
Section: Discussionmentioning
confidence: 99%
“… 73 The justification for these exclusions was rarely described and excluding such conditions may hinder CM practitioners whose patient population is characterised by a greater proportion of women, 74 GIT, 16 mental health co-morbidities 75 and chronic, complex conditions. 16 For example, no included articles justified the rationale for IBS exclusion. Prior research has shown IBS patients have a lower resting pressure of the lower oesophageal sphincter, 1 hyperalgesia of the oesophagus 76 and 50% of IBS patients have pathologic reflux.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 In present study, most of the ulcers were found in the pyloric region of stomach which is in consonant with Joseph Eichensher et al (2018)who discovered similar results that the common site of gastric ulcer is the pylorus on lesser curvature near the junction between body and antrum. 14 G cells produce peptide hormone Gastrin in pyloric antrum that activates the parietal cells to release hydrochloric acid.…”
Section: Discussionmentioning
confidence: 99%